Geochemistry and tectonic setting of late Precambrian volcanic and plutonic rocks in southeastern Cape Breton Island, Nova Scotia - Barr, Sandra M. (Canadian Journal of Earth Sciences, 1993)
Late Precambrian volcanic–sedimentary belts in the Mira (Avalon) terrane of southeastern Cape Breton Island display differences in rock types, petrochemistry, and age, showing that they did not form contemporaneously above a single northwest-dipping subduction zone, as proposed in earlier models. The oldest rocks are 680 Ma mafic and felsic flows and tuffs, and abundant, mainly tuffaceous, sedimentary rocks in the Stirling belt. They are interpreted to have formed in a trough within or peripheral to a volcanic-arc complex. Northwest of the Stirling belt, the East Bay Hills, Coxheath Hills, and Sporting Mountain belts consist of ca. 620 Ma mafic to felsic subaerial pyroclastic rocks and flows and contemporaneous dioritic to granitic plutons. Both volcanic and plutonic rocks are calc-alkalic to high-K calc-alkalic suites, formed in a continental margin volcanic arc. A correlative 620 Ma plutonic suite intruded the western margin of the Stirling belt, suggesting that subduction may have been toward the present southeast. The ca. 575 Ma Coastal belt, located southeast of the Stirling belt, is significantly younger than the other belts and appears to represent a less evolved calc-alkalic to low-K continental margin volcanic-arc and intra-arc basin formed above a northwest-dipping subduction zone. These various volcanic–sedimentary belts were juxtaposed by lateral movements along major faults in the late Precambrian to form this part of the Avalon composite terrane. Subduction-related, calc-alkalic magmatism at ca. 620 Ma was apparently widespread throughout the Avalon terrane of the northern Appalachian Orogen. However, ca. 680 Ma magmatism like that in the Stirling belt has been documented elsewhere only in the Connaigre Bay Group of Newfoundland. Circa 575 Ma and younger subduction-generated igneous activity like that in the Coastal belt has been recognized in southern New Brunswick, but alkaline magmas were forming in extensional regimes in other areas of the Avalon terrane at that time.